Vaccination in Developing Countries: A Review of Probable Factors for Lower Responses to Vaccine - Hiva Saffar; Mohammad Jafar Saffar; Hana Saffar (Mazandaran University of Medical Sciences, 2013)
Prevention of infectious diseases by immunization in children has markedly diminished the morbidity and mortality of once common ontagious diseases in many countries worldwide. Immunization programs have led to the global eradication of smallpox, elimination of measles and poliomyelitis in regions of the world, and substantial reduction in the morbidity and mortality attributed to diphtheria, tetanus, pertussis, and measles. Childhood vaccination was estimated to prevent more than 2.5 million deaths for vaccine preventable- diseases each year. However, at current levels of coverage, it still causes 1.7 million deaths annually, most of them in developing countries. The main objectives of this review are as following: To overview the expanded programme of immunization and WHO global vision and strategies for vaccination. To review underlying mechanisms that influence host immune response to vaccine, and differentiate primary from secondary vaccine failure. To determine the environmental factors that may reduce the potency of the vaccines or vaccinees. To explain the probable factors that lead to lower responses in vaccine recipients in developing countries.